2019
DOI: 10.1103/physrevlett.122.122301
|View full text |Cite
|
Sign up to set email alerts
|

Prescaling and Far-from-Equilibrium Hydrodynamics in the Quark-Gluon Plasma

Abstract: Prescaling is a far-from-equilibrium phenomenon which describes the rapid establishment of a universal scaling form of distributions much before the universal values of their scaling exponents are realized. We consider the example of the spatio-temporal evolution of the quark-gluon plasma explored in heavy-ion collisions at sufficiently high energies. Solving QCD kinetic theory with elastic and inelastic processes, we demonstrate that the gluon and quark distributions very quickly adapt a self-similar scaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 34 publications
10
51
0
Order By: Relevance
“…They are consistent with the numerically determined values in Eq. (16). We expect that, as in 3D [24], the inelastic scattering rate at the hard scale plays an important role as well.…”
Section: Scaling Behavior In a Kinetic Theory Picturementioning
confidence: 89%
See 2 more Smart Citations
“…They are consistent with the numerically determined values in Eq. (16). We expect that, as in 3D [24], the inelastic scattering rate at the hard scale plays an important role as well.…”
Section: Scaling Behavior In a Kinetic Theory Picturementioning
confidence: 89%
“…The mean values and error estimates quoted in Eqs. (15), (16) are obtained by combining and rounding the mean values and error estimates.…”
Section: Appendix A: Note On Initial Conditions In Coulomb Gaugementioning
confidence: 99%
See 1 more Smart Citation
“…When developing an understanding of the field theory side, the comparison to effective descriptions would be useful. Phenomena such as prescaling and far from equilibrium hydrodynamics [104] could be searched for; the applicability of fluid dynamics far from equilibrium [105] could be tested within our holographic model. It would furthermore be elucidating to consider different non-local observables, such as holographic entanglement entropy [21,64].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…These scaling laws have been discussed in the context of critical dynamics close to second-order phase transitions in equilibrium states over several decades. However, several theoretical studies have recently found the emergence of such dynamical scalings in isolated quantum systems even without critical points, and the universality are investigated from the perspective of NTFPs [47][48][49][50][51][52][53][54][72][73][74][75][76]. So far, the two experiments [55,56] report observations of the NTFP scenario in scalar and spinor Bose gases.…”
Section: Correlation Function and Dynamical Scalingmentioning
confidence: 99%